Standardisation Versus Adaptation in Canton’s Luxury Fashion Industry - Li, Yang (2009)
In view of the dynamic growth in the luxury market and the availability of luxury goods to a wider range of consumers than ever before, it is critically important for luxury researchers and marketers to understand why consumers buy luxury, what they believe luxury is and how their perception of luxury value impacts their buying behavior. In a global context, it is faced with a very important marketing decision: to standardise or to adapt its marketing mix? This study draws a wide range of literatures and primary data about the characteristics of Cantonese luxury market by using interviews and questionnaires, as well as case study methodology in order to determine the necessity of making appropriate market strategies for luxury brands in Canton. The case study approach was used to determine the extent of standardisation and adaptation of LVMH marketing mix and thus appropriate strategic recommendation was made on the basis of the segmented consumer behaviour in order to aid LVMH future success in Canton. Research results revealed that market segmentation was possible and important in a seemingly homogeneous Canton luxury market. This was proven when four segments of the luxury consumers were found: luxury lovers, luxury followers, luxury intellectuals and luxury laggards. Further, significant attitudinal differences towards key drivers of luxury consumption were found in all luxury consumer segments. Simultaneously in this study, it was important to adopt a case study approach to understand the degree of standardisation and adaptation of global luxury group LVMH’s marketing mix in the Cantonese market, where it was found that LVMH chose to standardize the core concepts of its products while adapting to the local market by infusing their products with local elements.